1982
DOI: 10.1111/j.1432-1033.1982.tb06919.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pulse‐Radiolysis Study of Cytochrome c3

Abstract: 1. Pulse-radiolysis experiments were performed in the presence of methyl viologen and cytochrome c3. After the pulse, methyl viologen radicals are formed and the kinetics of these radicals with cytochrome c3 are studied. The reaction between cytochrome c3 and methyl viologen radicals (MV') is diffusion controlled. The ionic strength dependence and the pH-dependence of this reaction were studied. From the ionic strength dependence (at pH 7.8) we found that the net charge of the fully oxidized cytochrome c3 mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 23 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…That particularly matters for the cases using hydrophilic mediators to bridge the electron flux between suspended cells and the electrode. Kinetically, it has been shown that the intramolecular electron transfer rate constant between the microbial membrane protein hemes can reach 10 5 –10 9 s −1 , [75–77] and the intermolecular electron transfer rate constant between the heme and external electron acceptor is also on the level of 10 8 M −1 s −1 [78] . All these considerations above raise critical concerns of the transmembrane electron transfer (via artificial or self‐secreted electron carriers) as the potential rate‐limiting step for the MET pathways.…”
Section: Cross‐membrane Transportation As a Key Process For Redox Med...mentioning
confidence: 99%
“…That particularly matters for the cases using hydrophilic mediators to bridge the electron flux between suspended cells and the electrode. Kinetically, it has been shown that the intramolecular electron transfer rate constant between the microbial membrane protein hemes can reach 10 5 –10 9 s −1 , [75–77] and the intermolecular electron transfer rate constant between the heme and external electron acceptor is also on the level of 10 8 M −1 s −1 [78] . All these considerations above raise critical concerns of the transmembrane electron transfer (via artificial or self‐secreted electron carriers) as the potential rate‐limiting step for the MET pathways.…”
Section: Cross‐membrane Transportation As a Key Process For Redox Med...mentioning
confidence: 99%